(untitled) (Journal of Parents and Teachers, 2026)
Among the ideas and experiences gathered here, we find what the French magazine Le Point has written about the 10 most stressful professions. Teaching ranks second. In addition, bridge has notable advantages in educational learning, and there are 6,000 French students who play it. When it comes to geography, the best teacher is undoubtedly Tintin, the hero of modern comics. As for reading, First World countries are not immune to failing grades in reading comprehension.